2016
DOI: 10.1016/j.bcmd.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Patients with type 1 Gaucher disease in Spain: A cross-sectional evaluation of health status

Abstract: A multicentre, cross-sectional epidemiological survey was conducted to describe the health status of patients with type 1 Gaucher disease (GD1) in Spain. Patient data were collected retrospectively from clinical records. Therapeutic goals for seven clinical parameters were chosen as primary outcome measures. 108 GD1 patients (mean age 44.8 years; 53% male) were recruited from 28 hospitals. Ninety-five patients (88%) were receiving treatment for GD1. Hemoglobin concentration was the therapeutic goal with the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 20 publications
4
28
0
Order By: Relevance
“…Our patient demographics were similar to that of the previously described Spanish cohort . Our group was slightly older (51.31 ± 14.4 years compared to 44.8 ± 16.6 years), men were 43% of our group, compared to 53%, and ERT was prescribed for 75% of our group, compared to 72% of the Spanish cohort.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our patient demographics were similar to that of the previously described Spanish cohort . Our group was slightly older (51.31 ± 14.4 years compared to 44.8 ± 16.6 years), men were 43% of our group, compared to 53%, and ERT was prescribed for 75% of our group, compared to 72% of the Spanish cohort.…”
Section: Discussionsupporting
confidence: 78%
“…Our patient demographics were similar to that of the previously described Spanish cohort. (22) Our group was slightly older (51.31 AE 14.4 years compared to 44.8 AE 16.6 years), men were 43% of our group, compared to 53%, and ERT was prescribed for 75% of our group, compared to 72% of the Spanish cohort. In the Spanish cohort, 36% of the patients had osteopenia or osteoporosis, whereas in our group 62% had osteopenia and 6% had osteoporosis.…”
Section: Discussionmentioning
confidence: 54%
“…Past studies involving adult patients (e.g. Giraldo, Solano, Pérez-Calvo, Giralt, & Rubio-Félix, 2005;Giraldo et al, 2016;Hayes et al, 1998;Masek et al, 1999) demonstrated the positive roles of symptom control, non-splenectomy and ERT in HRQoL assessments.…”
Section: Discussionmentioning
confidence: 99%
“… 45 > 16 Pompe disease [ 119 ] PGWBI Anxiety, depression, positive well-being, self-control, general health, vitality 22 > 18 PKU [ 133 ] PLC Emotional, practical and social impact, disease-specific symptoms, diet and therapeutic impact 40 Adolescents and adults Galactosemia [ 79 ], PKU [ 93 ] SIP-136 Sleep and rest, eating, work, home management, recreation and pastimes, ambulation, mobility, body care and movement, social interaction, alertness behavior, emotional behavior, communication 136 Adolescents, adults and elderly MELAS [ 69 ] SIP-68 Somatic autonomy, mobility control, mobility range, social behaviour, emotional stability, psychological autonomy/communication 68 Adolescents, adults and elderly Niemann-Pick disease type C [ 72 ] SF-36 Physical functioning, role limitations due to physical health, body pain, general health, vitality, social functioning, role limitations due to emotional problems, and mental health. 36 > 14 Acute porphyrias [ 68 ], carnitine palmitoyltransferase II deficiency [ 158 ], cystinuria [ 143 ], Fabry disease [ 52 57 , 87 , 92 , 107 111 , 132 , 141 , 145 , 147 , 159 162 ], familial hypercholesterolemia [ 95 , 112 ], Gaucher disease [ 60 , 61 , 98 , 99 , 113 , 114 , ...…”
Section: Resultsmentioning
confidence: 99%